Analysis about the use of educational videos to improve the pronunciation on the students from eighth grade in “Fernando Daquilema” high school during the academic period september 2020- july 2021 - Cepeda Naula, Raúl Diego (2021)
The study entitled "Analysis about the use of educational videos to improve the pronunciation on the students from Eighth grade in “Fernando Daquilema” High School during the academic period September 2020 - July 2021” was proposed considering the benefits videos offer. It is understood that the way how verbal and nonverbal factors are presented in videos makes students be in direct contact with authenticity in language usage. Therefore, the usage of videos enables students to enhance the quality of sound patterns and to improve fluency and accuracy diminishing at the same time the impact of the interlanguage phenomenon. In this context, analyzing their academic usage was the principal objective of this study. To accomplish this target, the interpretative research paradigm and the qualitative approach were adopted. Besides, the study fits the characteristics of a descriptive study where the Narrative-biographic and the ethnographic methods were used. For the data collection process, interviews were applied to students and the English teacher. For a deeper understanding of the phenomenon, some observations were also carried out. The results evidenced two remarkable facts; the first, participants are conscious of the benefits coming from the use of academic video, and not only for pronunciation or speaking but also for listening, grammar, and vocabulary expansion. The second, the post-viewing stage in the application process lacked some activities that probably would affect the accomplishment of the set objectives. It is concluded that videos are useful resources for pronunciation-based activities and offer innovative opportunities for formal and non-formal education.